Analysis of the possible consequences of large-scale production of sand and gravel mixture in the downstream of large hydroelectric facilities based on hydrodynamic modeling (the Votkinsk HPP as an example) - Anatoliy V. Lepikhin; Yuri S. Lyakhin; Alexey A. Tiunov; Anna A. Wozniak; Anton I. Luchnikov; Dmitiy V. Perepelitsa; Andrey V. Bogomolov (Водное хозяйство России: проблемы, технологии, управление)
The authors have presented estimation of possible hydraulic consequences of the large-scale mining of sand/gravel mixtures in the upper part of the Lower Kama Reservoir 9the Votkinsk Reservoir downstream) based on the multi-version computation experiments with the developed hydro/dynamic model of the water body under consideration. This estimation is necessary for development of measures aimed at minimization of negative aftermath and provision of the interest balance between water users.